Open Repair of Posterior Cruciate Ligament Tibial Bony Avulsion With Metal Anchor: A Case Report - Giovanni Bonaspetti; Stefano Tonolini; Giovanni Dib; Alessia Piovani (Case Reports in Orthopedics)
Conclusion: PCL bony avulsions are rare, and their optimal treatment remains a significant subject of debate, particularly in the skeletally immature patient. We believe that open repair with metal anchors could be a good choice to repair PCL bony tibial avulsion in patients without concomitant intra-articular lesions and immature growth plates or severe fragmentation.